Information Asymmetries in the Communication Between Bureaucracy and Citizens - Lubk, Claudia (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
Within OECD-countries, the public sector is among the largest employers. With an OECD-average of more than 19% of the total labour force being employed in the public sector, and bureaucracy being present in many aspects of everyday life, public administration plays an important role not only as an institution contributing to a functioning social market economy. As one of the main areas of interaction between citizens and “the State”, bureaucracy also considerably influences citizens’ image of the legislative and executive branch. The partly negative image that citizens have of the bureaucracy needs to be improved not only on that account, though. The interaction between citizens and bureaucracy largely impacts the utilisation of government programmes and measures, and therefore, their effectiveness. This text analyses current literature and applies theories from the field of institutional economics to show the influence of information asymmetries on the interaction between citizens and bureaucracy and discusses possible measures to improve the situation.
Keywords: asymetrie informacyjne; obywatele; biurokracja; ekonomia instytucjonalna